Optimizations studies on the microwave assisted synthesis of antimicrobial Peptaibols - Castro, Vânia I. B. (2013)
We present a systematic study on the best conditions to achieve the microwave-assisted solid phase peptide synthesis of a selected peptaibol, namely the pentapeptide Peptaibolin (Ac-Leu-Aib-Leu-Aib-Phol), by using several resins and different coupling and cleavage conditions aiming at a future synthesis of mimetics of larger members of the peptaibol family bearing bulkier unnatural α,α-dialkylglycines.